Where next for laterality research? Looking back and looking forward. Issue 3 (4th May 2021) - Beaton, Alan A.; Richards, Gareth
ABSTRACT: While paying attention to the recommendations of Ocklenburg, Berretz, Packheiser, and Friedrich (2020 ) in the target article, researchers in the field of laterality should attempt to: (1) solve the long-standing puzzle of the relationship between handedness and language lateralization; (2) further explore the genetic bases of manual and cerebral asymmetry and of their associations with psychiatric and neurodevelopmental conditions; (3) explore the adaptive significance of laterality for humans and non-humans and elucidate the relationships of asymmetry across species; and (4) embrace developing technologies to investigate the interaction between the hemispheres during the performance of everyday tasks.